Recursos minerais e o desenvolvimento econômico de Moçambique - Raitone Armando (2015)
Mineral resources are a backbone of the economy of many countries; they contribute significantly in share of GDP, employment, income, generating taxes, and for economic and social development. Literature has divided opinions among economic development analysts. Some point out that the existence of mineral resources in a country is a springboard for economic development, and others argue that the presence of mineral resources is a curse. The aim of this study is to analyze the development process of the Mozambican economy over the past 20 years and more specifically the role that the mineral economy has had and may have in this process of economic development. To achieve this goal, we compared the evolution of mineral production between the rest of the economy of the South, Centre and North regions and the country's economy from 1992 to 2012. The results indicate that the mineral sector has been growing more than the national economy and that of the South, Central and North regions; however, this sector contributes less than 2 % of GDP, with only 3% in tax revenue and employs less than 0.1% of the total national workforce. Although lately the mineral production is becoming a cornerstone in Mozambique's economy, its global market share in both reserves and production is only 0.1 %, excepting heavy minerals (ilmenite, rutile and zircon) that have their participation ranging from 1 to 9 %. Recent discoveries of graphite and natural gas in the North of Mozambique will put the country on a world leading position in the near future, which will require improvements of the legislative framework and management of royalties to reverse the current situation of low contribution in income and productivity of the national workforce.